2021
DOI: 10.1080/1547691x.2021.1905754
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mono-culture vs. Co-culture of keratinocytes and monocytes on cytokine responses induced by important skin sensitizers

Abstract: Sensitization to a contact allergen brings with it a lifelong risk to develop allergic contact dermatitis. Inflammation is an important part of the skin sensitizing mechanism, and understanding how different haptens stimulate the immune system, as well as the role played by different cell types present in skin, may be helpful for developing optimized in vitro models for risk assessment of new chemicals or mixtures. The aim of this study was to compare the cytokine profile following exposure of cells representi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…As a step forward in the validity of in vitro immunotoxicological assays, several co-culture assays are being developed and used ( Leonard et al, 2010 ; Noonan et al, 2019 ; Drasler et al, 2020 ; Karri et al, 2021 ). For example, an in vitro model of the inflamed intestinal mucosa, encompassing a three-dimensional co-culture of human intestinal epithelial cells (the cell line Caco-2) with human primary monocytes and monocyte-derived dendritic cells, can be used for assessing the effect of drugs and toxicants on gut inflammation ( Leonard et al, 2010 ).…”
Section: Models and Methods For Assessing Innate Immune And Innate Me...mentioning
confidence: 99%
“…As a step forward in the validity of in vitro immunotoxicological assays, several co-culture assays are being developed and used ( Leonard et al, 2010 ; Noonan et al, 2019 ; Drasler et al, 2020 ; Karri et al, 2021 ). For example, an in vitro model of the inflamed intestinal mucosa, encompassing a three-dimensional co-culture of human intestinal epithelial cells (the cell line Caco-2) with human primary monocytes and monocyte-derived dendritic cells, can be used for assessing the effect of drugs and toxicants on gut inflammation ( Leonard et al, 2010 ).…”
Section: Models and Methods For Assessing Innate Immune And Innate Me...mentioning
confidence: 99%
“…Traditional 2D skin models typically incorporate primary human or immortalized keratinocytes (such as HaCaTs), either in isolation, or co-cultured with other relevant cell types, (e.g. monocytes [ 110 ], or fibroblasts [ 111 ]). Such 2D models have been previously utilized to elucidate keratinocyte toxicity to molecules implicated in SJS/TEN pathogenesis, such as granulysin [ 26 ], TNF-α [ 78 ▪ ] and LL-37 [ 22 ].…”
Section: Development Of In-vitro/ex-vivo Models Of Stevens–johnson Sy...mentioning
confidence: 99%
“…Cao et al found that, compared with THP-1 cultured alone, THP-1 co-cultured with KCs expressed more CD86 and CD54 on their surface after being exposed to skin sensitizers [54]. Karri et al also compared the effects of KCs (HaCaT) and monocyte (THP-1), cultured alone with their co-culture, on cytokine responses induced by important skin sensitizers [55]. In the co-culture model, the secretion of IL-1β and IL-8 was significantly triggered by all tested haptens, while non-sensitizers and stimulants were not.…”
Section: Co-culture and 3d Modelmentioning
confidence: 99%